Od katolicyzmu do katolickości. W poszukiwaniu adekwatnej eklezjologii dialogicznej - Nadbrzeżny, Antoni (Verbum Vitae, 2023)
The aim of the article is to demonstrate the significance, meaning and need for a new type of thinking about the Church which has been described as a “dialogical ecclesiology”. This kind of ecclesiology responds to the call of the Second Vatican Council to build relations between the Church and the contemporary world based on the category of dialogue. The phrase “from Catholicism to Catholicity” suggests the need to move away from the defensive vision of the Church (referred to as Catholicism) towards the affirmation of the Church’s open and dialogical Catholicity. The elaboration of an adequate, coherent and credible dialogical ecclesiology requires a deeper rethinking of the meaning of the Church’s dialogical essence and a precise determination of the addressees, aspects and objectives of the ecclesial dialogue ad extra. While presenting the Church as a dialogical sacrament of salvation in history, the article combines theological (dogmatic) and existential perspectives. In particular, it takes into account the sensitivity of contemporary people to the phenomenon of suffering, which is difficult to accept but which – due to its universalism – may lead to a creative encounter between believers and atheists/ agnostics. In its theological message, the article is an expression of Christian hope, which also manifests its strength in today’s secularized “culture of the temporary”. It shows the value of an authentic meeting of people representing different religions and worldviews who, through fair dialogue, can discover the deeper meaning of their faith, existence and cooperation in defending the threatened humanity that is objectively the imago Dei.